Systems biology of cancer - Thiagalingam, Sam, 1957- (Cambridge : Cambridge University Press, 2015)
With over 200 types of cancer diagnosed to date, researchers the world over have been forced to rapidly update their understanding of the biology of cancer. In fact, only the study of the basic cellular processes, and how these are altered in cancer cells, can ultimately provide a background for rational therapies. Bringing together the state-of-the-art contributions of international experts, Systems Biology of Cancer proposes an ultimate research goal for the whole scientific community: exploiting systems biology to generate in-depth knowledge based on blueprints that are unique to each type of cancer. Readers are provided with a realistic view of what is known and what is yet to be uncovered on the aberrations in the fundamental biological processes, deregulation of major signaling networks, alterations in major cancers and the strategies for using the scientific knowledge for effective diagnosis, prognosis and drug discovery to improve public health.
Part 1: Introduction to modular organization of the networks of gene functions and cancer ; Part 2: Alterations in the regulatory networks of cellular and molecular events ; Part 3: Events responsible for aberrant genetic and epigenetic codes in cancer ; Part 4: Functional networks of events that modulate phenotypic manifestation of cancer ; Part 5: Current state of the evolving MMMN cancer progression models of cancer ; Part 6: Applications of comprehensive cancer progression models in the fight against cancer.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cancer -- Genetic aspects; Systems biology